Electrical and Mechanical Activity of The Heart - Erdiansyah Zulyadaini; Hariadi Hariawan; Budi Yuli Setianto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
The regularity and rhythm of contraction of the heart muscles (myocardium) depends on how electrical impulses spreads through the conduction system organized. The process is initiated by electrical stimulation which thencauses depolarization. Depolarization is a series of ion transfer through channels that are specifi c to myocardial cell membrane (sarcolemma). These canals spread across the sarcolemma, which include:the Na+ channels, Ca2+ channels, channelK+, Na+-Ca2+exchanger, Na+-K+-ATPase pump and Ca2+active pump. The infl ux of Na+ ions into cell will start depolarization and then spread through conduction system to the rest of the myocardium.